Uruk, Irak. Feldforschungen 2017 und 2018 - van Ess, Margarete (e-Forschungsberichte des DAI, 2019)
Since 2015, activities have been resumed at the site in Uruk in southern Iraq. Both, the continuation of the scientific research in the ruin and the preservation and presentation of what has already been excavated, has been the focus. In particular, conservation and presentation concepts have been worked out in detail in close cooperation with the responsible Iraqi authorities. Scientific research resumed in newly selected excavation areas. All activities serve as a training area for the programme "Iraqi-German Expert Forum on Cultural Heritage" funded within the framework of the Archaeological Heritage Network of the German Federal Foreign Office and the German Archaeological Institute.